Upaya Meningkatkan Kompetensi Guru Menerapkan Nilai-nilai Luhur Budaya dalam Pembelajaran Melalui Supervisi Klinis di SD Jetis - Sri Wahyuni (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
Effort to Improve the Competence of Teachers Applying Cultural Values in Learning Through Clinical Supervision in Jetis SD Lesson year 2018/2019.The objectives of this study are (1) Carry out clinical supervision to improve teacher competency in implementing the noble values ​​of culture in learning at SD Jetis. (2) Knowing the increase in teacher competence in applying the noble values ​​of culture in learning at SD Jetis.This study uses school action research. The research was conducted in two cycles, each cycle consisting of four stages, namely: planning, implementation, observation, and reflection. The target of the study was the 6th grade teacher of SD Jetis which numbered three people in the 2018/2019 academic year. Data obtained through observations about the implementation of clinical supervision, RPP documents, and implementation of learning.The results of this study are (1) The teacher can arrange an implementation plan to insert the noble cultural values. This can be seen from the RPP products prepared by the teacher getting scores in good categories and increasing from cycle 1 to cycle 2 by 8% (2) Teachers can carry out learning by applying the noble values ​​of culture with good category results and there is an increase of 9% from cycle 1 to cycle 2. Thus, it shows that through clinical supervision the competence of Jetis elementary school teachers in applying the noble values ​​of culture in learning can increase.